Apperceptions of the Ireng Mask Dance and Finger Painting as Means of Self-Expression in Early Childhood (Observation Study at Pertiwi Bojong Kindergarten and Pertiwi Rambaenak Kindergarten) - Rahajeng Silmi Nuswantari; Joko Pamungkas (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Early childhood is a crucial period in a child's development, including self-expression. One way to help children channel their emotions, imagination, and thoughts is through artistic activities. This study observed two artistic activities, namely Ireng Mask Dance and finger painting, which were implemented at Pertiwi Bojong Kindergarten and Pertiwi Rambaenak Kindergarten in Magelang Regency. The aim was to see how these two activities could serve as a means for children to express themselves. Using a descriptive qualitative approach through direct observation, the results showed that while both activities have great potential, their implementation still faces challenges, such as teachers' lack of understanding in guiding children's creative processes, limited resources, and insufficient integration of local culture into learning. This study suggests the need for teacher training, the development of more varied media, and more contextual learning modules to ensure that art activities can truly support children's holistic development.